“Êxule Sísifo”: a metáfora do não pertencimento nos poemas “Paris-Texas” e “O Doublé”, de José Antônio Assunção - Leite, Jonas Jefferson de Souza (Revista Leitura, 2019)
“Exiled Sisyphus”: the non-belonging metaphor in the poems “Paris-Texas” and “O Doublé”, by José Antônio Assunção DOI: 10.28998/2317-9945.2019n63p322-325